The structural determinants of checkpoint activation - MacDougall, Christina A; Byun, Tony S; Van, Christopher; Yee, Muh-ching; Cimprich, Karlene A (Genes & development, 2007)
Here, we demonstrate that primed, single-stranded DNA (ssDNA) is sufficient for activation of the ATR-dependent checkpoint pathway in Xenopus egg extracts. Using this structure, we define the contribution of the 5'- and 3'-primer ends to Chk1 activation when replication is blocked and ongoing. In addition, we show that although ssDNA is not sufficient for checkpoint activation, the amount of ssDNA adjacent to the primer influences the level of Chk1 phosphorylation. These observations define the minimal DNA requirements for checkpoint activation and suggest that primed ssDNA represents a common checkpoint activating-structure formed following many types of damage.